2015
DOI: 10.1016/s0924-9338(15)30383-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Development of Alcohol Dependence

Abstract: Introduction: The present study was aimed to confirm that a family history of alcoholism and early alcohol initiation are the factors associated with the development of alcohol dependence. Subjects and methods: The study was based on authors` anonymous questionnaire. In the index group there were 125 people, aged 22-68, members of AA groups. In the control group there were 231 people, aged 17-65, with no history of alcoholism. The results were considered as significant with a p value < 0.05. Statistical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Studies have also shown a relationship between externalising and internalising disorders in adolescents and mental disorders or alcohol/psychoactive substance dependence in one or both parents (Bratek et al, 2013). Adolescents who witness domestic violence are more likely to develop anxiety disorders or PTSD and aggressive behaviours.…”
Section: Relationships Between Adverse Childhood Experiences and Ment...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also shown a relationship between externalising and internalising disorders in adolescents and mental disorders or alcohol/psychoactive substance dependence in one or both parents (Bratek et al, 2013). Adolescents who witness domestic violence are more likely to develop anxiety disorders or PTSD and aggressive behaviours.…”
Section: Relationships Between Adverse Childhood Experiences and Ment...mentioning
confidence: 99%
“…Research has also shown a strong relationship between physical, emotional and sexual abuse and suicidal behaviour in adolescents. The highest risk of suicidal thoughts in psychoaktywnych u jednego lub obojga rodziców (Bratek et al, 2013). Wśród nastolatków będących świadkami przemocy w rodzinie częściej stwierdza się zaburzenia lękowe lub PTSD i zachowania agresywne.…”
Section: Relationships Between Adverse Childhood Experiences and Suic...unclassified
“…Previous studies have linked earlier age of alcohol initiation with the greatest risk of future alcohol abuse and/or dependence [19][20][21][22], particularly among those who consume a full standard alcoholic drink before age 15 [7,8]. However, research has been limited by several methodological issues.…”
Section: Introductionmentioning
confidence: 99%